"Just Let Me Go": End-of-Life Planning Among Ojibwe Elders. (6th December 2016) - Dennis, Mary Kate; Washington, Karla T
Abstract: Purpose of the Study: Although advance care planning (ACP) is designed to promote person-centered end-of-life care, the principles underpinning it are at odds with the values and norms of many American Indian/Alaska Native (AI/AN) communities, contributing to low rates of ACP among AI/AN elders. The purpose of this study was to explore the apparent tension between Western approaches to end-of-life care, including its emphasis on ACP, and the expectations and wishes of one community of AI elders, in hopes of informing more culturally appropriate approaches to planning for end-of-life care. Design and Methods: About 20 tribal elders living on a Great Lakes reservation participated in semistructured, face-to-face interviews. Participants were recruited through convenience and snowball sampling techniques. The interviews were analyzed using an inductive thematic analysis approach. Results: Despite seeing little need for ACP, the elders were generally open to discussing the care they would want at end of life. Many were readily able to describe their wishes for a peaceful death and had already developed funeral and burial or cremation plans. Although establishing one's individual legacy was not a salient end-of-life concern for the elders, several found meaning in describing their contributions to preserving their families, the community, and their cultural lifeways. Implications: A lack of formal ACP within AI/AN communities does not necessarily reflect a cultural aversion to discussing preferences for end of life. Efforts to increase ACP in tribal communities would likely be enhanced by acknowledgment of the spiritual and cultural significance of death and dying for many AI/AN individuals.